Physiotherapy Management of low back pain with Sacroiliac Joint Component; A case report - C.O. Adesola; A.A. Babatunde; U. Ushotanele (AOSIS, 2014)
This report describes a clinical case of 71 year old man with low back pain of sacroiliac joint component.